PEMBERDAYAAN APARATUR DESA DALAM PENGEMBANGAN KAWASAN WISATA YANG BERWAWASAN SOSIAL LINGKUNGAN DI DESA SILALAHI II KECAMATAN SILAHISABUNGAN KABUPATEN DAIRI - R. Hamdani Harahap1 (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2022)
The tourism development of Silalahi II Village is still constrained in various aspects that touch tourism services, for example: serving guests/visitors with humility, hospitality, providing halal culinary delights with delicious and clean flavors, availability of adequate infrastructure, maintaining environmental cleanliness from the generation of organic waste and non-organic originating from household waste and dry leaves and animal waste scattered along village roads. This condition needs to be followed up by conducting community service programs. This activity is carried out to change the mindset of the community in providing alternative tourism services. The purpose of this regular mono year community service activity is to empower the Silalahi II Village Apparatus through training on changing the mindset of tourism services, training in creative and innovative thinking and training in the management of tourist areas based on environmental social values in creating a clean and healthy tourist village. The empowerment of village apparatus is something urgent at this time, because the problem of powerlessness that arises is the inability to develop the potential of local resources, especially in developing the potential of assets that become existing resources. It is hoped that the Silalahi II Village Apparatus will be able to become a catalyst together with the community. To achieve this goal, the methods used in this activity are: Socialization and Tourism Development Training, Participatory Organizing, Monitoring and Evaluation. The achievement of this regular year mono is that the partner group (village apparatus) is able to become a driving force for the community through the empowerment of the village apparatus as a sustainable tourism area developer. Keywords: Tourism Development; Changes in Mindset, Potential of Local Resources; Empowerment of Village Apparatus; Based on Social Environment